Overlap of Functional Gastrointestinal Disorders: Common Mechanisms of Pathogenesis as a Key to Rational Therapy - S. N. Mekhdiyev; O. A. Mekhdieva; O. M. Berko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to review the common risk factors and links in the pathogenesis of functional gastrointestinal disorders (FGID) to optimize therapy of patients with a combination of multiple FGID.Key points. FGID occurs in more than 40 % of people globally, mainly affecting the working-age population in young and middle-aged subjects. At the same time, more than 30 % of patients have a combination of 2 or more functional gastrointestinal (GI) disorders i.e. overlap syndrome. Common links in the pathogenesis of FGID include disorders of gut-brain interaction, visceral hypersensitivity, changes in intestinal microbiota, overproduction of proinflammatory cytokines, impaired epithelial permeability and motor activity of the gastrointestinal tract. The combination of FGID in various gastrointestinal segments is associated with more pronounced clinical symptoms (mutual burden syndrome). Common risk factors and pathogenetic links of the functional disorders enables reducing the number of prescribed medications when several FGIDs overlap in one patient, which also increases adherence to therapy. Treatment of FGID includes adjustment of risk factors and drug therapy. As a pathogenetically justified pharmacotherapy of overlap syndrome, Kolofort, highly diluted antibodies to TNF-α, histamine and brain-specific protein S-100, is of interest.Conclusion. Kolofort has demonstrated high efficacy and safety including among patients with overlap FGID enabling to consider it as the treatment of choice in these patients.